ANALISIS POTENSI INVESTASI DI KOTA SEMARANG - Hardiwinoto -; Andwiani Sinarasri; Akhmad Fathurrohman (Universitas Muhammadiyah Semarang, 2014)
The research aims to identify potencial investment in the city of Semarang. The method used to survey about baseline economic activity and identification of potential investment to the stakeholders with the investment both private and government in the city of Semarang. The method of analysis used is suvey and discriptive statistic. The analytical methods to determinethe potential investment in the city of Semarang. The results of the study are known potencial investment of Semarang City accordance with the location, type and sources of investment financing.